2001
DOI: 10.1083/jcb.200103105
|View full text |Cite
|
Sign up to set email alerts
|

Contraction and polymerization cooperate to assemble and close actomyosin rings around Xenopus oocyte wounds

Abstract: Xenopus oocytes assemble an array of F-actin and myosin 2 around plasma membrane wounds. We analyzed this process in living oocytes using confocal time-lapse (four-dimensional) microscopy. Closure of wounds requires assembly and contraction of a classic “contractile ring” composed of F-actin and myosin 2. However, this ring works in concert with a 5–10-μm wide “zone” of localized actin and myosin 2 assembly. The zone forms before the ring and can be uncoupled from the ring by inhibition of cortical flow and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
175
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 151 publications
(187 citation statements)
references
References 41 publications
(52 reference statements)
11
175
1
Order By: Relevance
“…Fluorescent intensities were measured using Image J 1.37v or Adobe Photoshop 7.0. Flow rates were extracted from the slopes of kymographs as previously described in Mandato and Bement [2001]. Quantifications of fluorescence intensities at the leading edge, trailing edge, or on the contractile ring itself were measured at multiple locations and subsequently averaged.…”
Section: Imaging Photoactivation and Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent intensities were measured using Image J 1.37v or Adobe Photoshop 7.0. Flow rates were extracted from the slopes of kymographs as previously described in Mandato and Bement [2001]. Quantifications of fluorescence intensities at the leading edge, trailing edge, or on the contractile ring itself were measured at multiple locations and subsequently averaged.…”
Section: Imaging Photoactivation and Image Analysismentioning
confidence: 99%
“…This system is ideal for such an analysis in that it was previously found that the actin array that forms in response to wounding is comprised of pools of highly dynamic and relatively stable F-actin that are spatially distinct. That is, dynamic actin structures such as F-actin comets form around the outer portion of the ring, while relatively stable F-actin concentrates on the interior of the ring [Mandato and Bement, 2001]. Each of these populations has different labeling characteristics: the pool of dynamic actin is efficiently labeled by fluorescent actin and poorly labeled by fluorescent phalloidin in living cells, while the pool of stable actin is efficiently labeled by fluorescent phalloidin and poorly labeled by fluorescent actin Bement, 2001, 2003].…”
Section: Distinguishing Between Stable and Dynamic Actin In Living Cellsmentioning
confidence: 99%
“…(3) In this model system, PM damage elicits actin and myosin-2 assembly in a precisely bounded zone around wound borders. (16) The actomyosin array segregates over time: while F-actin assembles throughout the wound array, myosin-2 becomes enriched on the interior circumference. (17) Subsequent studies showed that Rho GTPases direct the actomyosin response during wound healing and are likely responsible for the observed segregation of the actomyosin array.…”
Section: Rho Gtpase Activity Zonesmentioning
confidence: 99%
“…During oocyte wound healing, for example, myosin-2 concentrates on the interior of the actomyosin array, while dynamic actin is concentrated around the outside of the array. (16,17) That this segregation results from the segregation of the Cdc42 and Rho activity zones is indicated both by the timing of segregation and the effects of experimentally broadening the Rho zone. (3) This raises a further question, namely, why segregate different components of the contractile array?…”
Section: Contributions Of the Zones To Contractile Arraysmentioning
confidence: 99%
“…This can occur in vivo either due to the coincidence of a cofilinactin and actin-DNase I and/or the existence of cofilin-actin-DNase I ternary complex. Similar techniques have been used previously to demonstrate interactions between actin and myosin [30] and the formation of complexes between the ABPs a-actinin and Nspl1 [31] as well as between insulin and its associated receptor [32].…”
Section: Discussionmentioning
confidence: 95%